A Dynamic Reconfiguration Scheme for Embedded System Based on Multi-core DSP. Issue 4 (March 2021) - Liu, Xiaojian; Liu, Shuo; Lv, Hao
Abstract: High-performance embedded system is needed in high-speed and accurate avionics control systems, but its hardware resources are limited. It is of great significance to reuse hardware resource through static or dynamic reconfiguration. A dynamic local reconfiguration scheme is designed based on c6678 isomorphic multi-core DSP to realize the dynamic reconfiguration of software on a single core under the premise of ensuring the normal operation of the whole system. This reconfiguration scheme can realize the complete switching of software on the whole core and realize the time division multiplexing of multiple algorithms in the same memory space. Experimental results show that the scheme can fully meet the requirements of real-time.